Skiing Trauma and Safety: Twelfth Volume 1999
DOI: 10.1520/stp12353s
|View full text |Cite
|
Sign up to set email alerts
|

Vision—An Essential Factor for Safety in Skiing: Perception, Reaction, and Motion Control Aspects

Abstract: Observation and perception errors in combination with lack of attention explain the majority of all falls in skiing. This associates vision and vision deficiencies with safety aspects in skiing. The purpose of this study was to determine the effect of reduced visual acuity on the reaction time of a skier in safety-critical skiing situations. For this purpose, field experiments were conducted in the 1995/96 winter season. The subjects had to pass over a prepared ledge in the terrain and react to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…Peripheral vision is an essential factor for safety in alpine skiing. 10 Skiers are advised to moderate speed on visibility considering the rules of the International Ski Federation to avoid collisions with other skiers. Collisions frequently lead to polytrauma and are likely to involve the head.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral vision is an essential factor for safety in alpine skiing. 10 Skiers are advised to moderate speed on visibility considering the rules of the International Ski Federation to avoid collisions with other skiers. Collisions frequently lead to polytrauma and are likely to involve the head.…”
Section: Discussionmentioning
confidence: 99%
“…However, ski helmet use seems to be related to various factors, as studies have demonstrated that helmet use was more frequent among younger compared with older age groups, locals compared with tourists, as well as skilled skiers compared with less skilled skiers [ 16 , 21 ] . A common reason reported for helmet non-use is a limited fi eld of vision [ 5 , 14 ] , and peripheral vision is an essential factor for safety in alpine skiing [ 19 ] . According to the rules of the International Ski Federation, skiers and snowboarders are advised to adjust their speeds based on visibility [ 8 ] .…”
mentioning
confidence: 99%
“…Even though our results indicate that ski goggles increase reaction time to peripheral vision, we still recommend the use of ski goggles during skiing or snowboarding for their protection against ultra violet light [ 1 ] and tearing of the eyes due to the air stream, which may lead to diminished vision. Such reduced visual acuity could increase reaction times to even more dangerous situations, like avoiding ice patches on ski slopes [ 19 ] . An important limitation must be considered when interpreting our results, which is the use of a laboratory situation in a quiet environment.…”
mentioning
confidence: 99%
“…The visual deficiencies created by foggy goggles, inappropriate lens colour, or no optical correction may account for injury on poor visibility days. Decreased visual acuity has been found to delay reaction-times and the ability to take evasive action [36][37][38]. Regular eye testing and wearing prescription eyewear whilst skiing or snowboarding has been included in the strategy.…”
Section: Discussionmentioning
confidence: 99%